Sifat Fungsional dan Tingkat Penerimaan Masyarakat Atas Produk Olahan Labu Susu (Cucurbita moscatta ‘Butternut’) sebagai Upaya Pencegahan Anemia dan Stunting - Nurpuji Mumpuni; Yuli Astuti; Dewi Zolekhah; Budi Setiadi Daryono; Supriyadi Supriyadi; Lily Arsanti Lestari (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Anemia and stunting remain a major challenge in public health issues, especially in pregnant women and toddlers. Cucurbita moscatta ‘Butternut’ (Labu susu), which is rich in essential micronutrients uch as Beta Carotene (provitamin A), folic acid, iron, and zinc, can be processed into highly potent functional foods. Aside from being an excellent source of alternative carbohydrates, it can also meet the micronutrient needs to support the prevention of Anemia and stunting. This activity was carried out at the Community-Friendly Green Open Space (RTH - Ruang Terbuka Hijau) in the Bener sub-district, Tegalrejo district, Yogyakarta City, with the aim of analyzing the taste acceptability of processed bottle gourd products among the target groups. The implementation methods included socialization, taste testing, and acceptability analysis of three processed products based on Bottle Gourd: Nutrient-Rich Baby Porridge, High-Protein Mud Cake (Kue Lumpur), and Compote for Pregnant Women (Kolak Ibu Hamil). The activity involved 50 panelists who assessed the color, aroma, taste, texture, and overall acceptance of the three processed products using a six-level hedonic scale. The results showed that all three products were well-received. For all indicators ( Color, Aroma, Taste, and Texture), all products received scores above 4.6, and the overall acceptance was above 5. The overall acceptance score for the High-Protein Mud Cake (5.22 ± 0.6), the Kolak for Pregnant Women (5.18 ± 0.7), and Nutrient-Rich Baby Porridge (5.00 ± 0.8). The conclusion of this research is that panellists “like” and “accept / receive” all three products. This activity had a positive impact on increasing public knowledge regarding the diversification of local food and served as a strategic rocessed products; step in the effort to prevent anemia and stunting at the family level through the fulfillment of essential micronutrients.